New records of the rare dragonfly, Black Pennant – Selysiothemis nigra (Vander Linden, 1825) (Insecta: Odonata) in Bosnia and Herzegovina - Toni Koren; Domen Trkov; Kaja Vukotić; Mitja Črne (Natura Sloveniae)
In 2012, we recorded a Black Pennant, Selysiothemis nigra, at two sites in Bosnia and Herzegovina, i.e. in the surroundings of Klepci village and in Hutovo Blato Nature Park, Neretva River. These are the first recent records of this species in Bosnia and Herzegovina, which had previously been known only from the entomological collection in the Museum of Sarajevo. As this species had previously been recorded on the Croatian side of the Neretva River, these records fit into the distribution area of the species. With the confirmation of this record, the dragonfly fauna of Bosnia and Herzegovina consists of 60 species.